Bingeing on High‐Fat Food Enhances Evoked Dopamine Release and Reduces Dopamine Uptake in the Nucleus Accumbens. Issue 4 (3rd March 2021) - Jones, Sara R.; Fordahl, Steve C.
Abstract : Objective: Binge‐eating disorder (BED) disrupts dopamine neuron function, in part by altering dopamine transporter (DAT) activity. This study characterized the effects of high‐fat bingeing on presynaptic dopamine terminals and tested the hypothesis that acute low‐dose amphetamine would restore DAT function. Methods: C57BL/6 mice were given limited access (LimA) to a high‐fat diet (2 h/d, 3 d/wk) or standard chow (control). After 6 weeks, ex vivo fast‐scan cyclic voltammetry was used to characterize dopamine‐terminal adaptations in the nucleus accumbens. Prior to undergoing fast‐scan cyclic voltammetry, some mice from each group were given amphetamine (0.5 mg/kg intraperitoneally). Results: Escalation of high fat intake, termed bingeing, occurred in the LimA group and coincided with increased phasic dopamine release, reduced dopamine uptake rates, and increased dopamine receptor 2 (D2 ) autoreceptor function. Acute amphetamine selectively reversed dopamine uptake changes in the LimA group and restored the potency of amphetamine to inhibit uptake. Conclusions: High‐fat bingeing enhanced dopaminergic signaling in the nucleus accumbens by promoting phasic dopamine release and reducing clearance. This study's data show that amphetamine was efficacious in restoring impaired DAT function caused by high‐fat bingeing but did not reduce dopamine release to normal. These presynaptic changes should be considered if amphetamine‐like dopamine releasers are used as treatments for BED.